The Implementation of People's Republic of China's Maritime Security Strategy to Protect Its Energy Security in the Indian Ocean Region (2015-2019) - Anak Agung Perwita (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2020)
Korea is a country that once full of doubts. As time goes by, every sector from Korea are turns out to be huge achievements of the Korean people. Korean pop culture for instance, becomes a crucial driver for Korean economy. Not only Korean pop culture, recently property investor from Korea also becomes a big player in the US, and moreover in the global stage. New study also tells that Korea as global property industry player could exceed China as China’s economy slowing down. Therefore, question how can South Korea's property industry sectors thrive overseas, such as in the U.S.? Arises. This paper would explain the factors behind South Korean property industry performance in US, including push and pull factors through a scope of global capital movement paradigm. Meaningful government supports, big possibilities, and a good investment climate for South Korean property industry plus the right global demands could be some factors behind the rising of South Korean property industry, especially in the US. Keyword(s): Korea, Property, Industry, Push and Pull Factors, Global Capital Movement